2001
DOI: 10.1128/aac.45.6.1860-1867.2001
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activities of Ertapenem (MK-0826) against Recent Clinical Bacteria Collected in Europe and Australia

Abstract: Ertapenem (MK-0826, L-749,345) is a 1-␤-methyl carbapenem with a long serum half-life. Its in vitro activitywas determined by broth microdilution against 3,478 bacteria from 12 centers in Europe and Australia, with imipenem, cefepime, ceftriaxone, and piperacillin-tazobactam used as comparators. Ertapenem was the most active agent tested against members of the family Enterobacteriaceae, with MICs at which 90% of isolates are inhibited (MIC 90 s) of <1 g/ml for all species. Ertapenem also was more active than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
51
1
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(60 citation statements)
references
References 19 publications
2
51
1
6
Order By: Relevance
“…These findings are similar to those from European, Australian, and American studies (4,6,7). However, ertapenem was less active against Acinetobacter spp.…”
supporting
confidence: 80%
“…These findings are similar to those from European, Australian, and American studies (4,6,7). However, ertapenem was less active against Acinetobacter spp.…”
supporting
confidence: 80%
“…Several studies have shown that most members of the family Enterobacteriaceae are highly susceptible to ertapenem, including isolates resistant to several other antimicrobial agents (6,9). In this study, members of the family Enterobacteriaceae, all of which were susceptible to ertapenem, accounted for 93.0% of all isolates from microbiologically evaluable patients in both treatment groups.…”
Section: Discussionmentioning
confidence: 80%
“…Ertapenem (formerly MK-0826; Merck & Co., Inc.) is a once a day parenteral ␤-lactam agent with excellent in vitro activity against many gram-positive and gram-negative aerobes and anaerobes generally associated with community-acquired infections, including most members of the family Enterobacteriaceae, pathogens most commonly responsible for UTIs (6,9). Ertapenem is not indicated for Pseudomonas aeruginosa or enterococci, which are more often associated with nosocomial infections.…”
mentioning
confidence: 99%
“…By taking into account the fact that a T Ͼ MIC of 30 to 40% is required for ertapenem and that a T Ͼ MIC of 60 to 70% is required for ceftriaxone and the fact that both antibiotics exhibit free fractions between 5 and 10% in the therapeutic concentration range (6,10), the directly measured concentration of ertapenem at 12 h (11.8 mg/liter) can be compared with the concentration of ceftriaxone at 24 h (10.3 mg/liter). The interpretation of these data in the context of the MICs of ceftriaxone and ertapenem at which 90% of isolates are inhibited, obtained in a large multicenter surveillance study (5), revealed that both antibiotics have comparable pharmacokinetic-pharmacodynamic parameters for Moraxella spp., pneumococci, and Haemophilus influenzae, the most frequent pathogens causing community-acquired pneumonia. The pharmacokinetic-pharmacodynamic parameters for ertapenem were particularly favorable for activity against Staphylococcus aureus, a more frequent cause of pneumonia in elderly people and patients with comorbidities.…”
Section: Discussionmentioning
confidence: 99%